Groundwater recharge influencing the arsenic enrichment in the aquifer of west Bengal - Singh, Neha; Sen, Ratan; Vishwakarma, Chandrashekhar Azad; Asthana, Harshita; Mukherjee, Saumitra (International Journal of Advanced Geosciences, 2016)
Arsenic contamination, a very serious issue, has a detrimental effect on the living being. Arsenic contamination is found in the Gangetic plains, with West Bengal as the most affected state. In the present study, an attempt has been made to use weighted overlay analysis for arsenic hazard zonation based on the factors that influence the groundwater in a terrain. Weighted overlay analysis was done for mapping the arsenic contamination zone by assigning weightage and rating to geomorphology, land use/land cover, soil type, cropping intensity, slope and drainage density in North 24 Parganas. The whole region has been formed by the sedimentation from the river, and soil at the surface contains higher concentration of arsenic. Arsenic may get released from the sediment by various mechanism and transport downward along with the infiltration of rainwater. Thus, arsenic contamination in groundwater is influenced by the arsenic rich sediments, slope, and drainage pattern of the area. The arsenic concentration in collected groundwater samples shows the same result as obtained from the weighted overlay analysis except in the area with deeper water level. Thus, weighted overlay analysis along with water level data can be an effective method for determining the risk of arsenic in an area.